RANCANG BANGUN PROGRAM SCIENCE PADA RUMUS DAN SOAL MATEMATIKA UNTUK KELAS VI SD - Renal Verdiyan Erlangga; Ita Dewi Sintawati; Omar Pahlevi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Mathematics is one of the scary and difficult lessons at all levels of education. The method of learning mathematics is one of the factors that causes students not to like this lesson. So far textual learning methods that tend to be boring. For this reason, the writer made a mathematical formula and problem program using desktop-based Java Netbeens 8.2, especially for elementary school class VI, because it would face USBN. It is hoped that with the creation of this mathematics program, elementary school students in grade VI can understand formulas and math problems easily. This program displays mathematics material in class VI, examples of questions accompanied by ways to work on the questions, and questions that can be directly filled in by the user and the results will appear immediately, so the user can find out how many questions are answered correct and how many questions answered incorrectly. The existence of this program is expected to help elementary school students to get used to learning to use computers or laptops, and as a means to practice computer-based national exams.